Terapi Spiritual Emotional Freedom Technique (Seft) Mempengaruhi Kualitas Tidur dan Kecemasan pada Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa di Rumah Sakit Pertamina Bintang Amin Kota Bandar Lampung - Endah Fajrianti; Djuniar Djamaludin; Eka Yudha Chrisanto (Malahayati Nursing Journal, 2025)
ABSTRACT According to the World Health Organization (WHO) in 2020. Kidney disease is 1 of the 10 main causes of death in the world. This kidney disease has increased from being ranked 13th cause of death in the world to ranking 10th in 2019. According to data from the Indonesian Ministry of Health (2019). The prevalence of chronic kidney failure in Indonesia continues to increase from 2.0% in 2013 to 3.8% in 2018. Hemodialysis (HD) therapy in CKD patients takes a long time and can repeatedly cause physical and mental problems such as anxiety and quality problems. Sleep. One non-pharmacological intervention that can be used to overcome this problem is by using Spiritual Emotional Freedom Technique (SEFT) Therapy. SEFT therapy is a type of therapy that combines mind-body by pressing the body's meridian points.The effect of Spiritual Emotional Freedom Technique (SEFT) therapy on sleep quality and anxiety in chronic renal failure patients undergoing hemodialysis.This research uses the Quasy Experiment method with a One Group Pre-Post Test. This research was conducted on 30 respondents using purposive sampling technique. The research instrument used a sleep quality questionnaire, namely the Pittsburgh Sleep Quality Index (PSQI) questionnaire and an anxiety questionnaire, namely the Hamilton Anxiety Rating Scale (HARS) questionnaire and research therapy used Spiritual Emotional Freedom Technique (SEFT) therapy. Data analysis used univariate and bivariate analysis with the t-dependent test.The results of statistical tests of sleep quality pre-test (8.60 ± 2.027) and post-test (4.77 ± 1.870) while of pre-test anxiety (21.37±4.664) and post-test (15.63±5.690).The p-value obtained is 0.000.There is a significant influence between  Spiritial Emotional Freedom Technique (SEFT) therapy on sleep quality and anxiety in chronic renal failure patients undergoing hemodialysis at Pertamina Bintang Amin Hospital, Bandar Lampung City. Keywords: Renal Failure, Hemodialysis, SEFT Therapy, Sleep quality, Anxiety       ABSTRAK Menurut World Health Organization (WHO) tahun (2020). Penyakit Ginjal merupakan 1 dari 10 penyebab utama kematian di dunia. Penyakit ginjal ini telah meningkat dari peringkat 13 penyebab kematian di dunia menjadi peringkat ke 10 pada tahun 2019. Menurut data Kementerian Kesehatan Republik Indonesia (2019). Prevalensi gagal ginjal kronik di Indonesia terus meningkat dari 2,0% pada tahun 2013 menjadi 3,8% pada tahun 2018.Terapi hemodialisa (HD) pada pasien GGK membutuhkan waktu yang lama dan berulang dapat menyebabkan masalah fisik dan mental seperti kecemasan dan masalah kualitas tidur. Salah satu intervensi nonfarmakologi yang dapat digunakan untuk mengatasi masalah tersebut yaitu dengan menggunakan Terapi Spiritual Emotional Freedom Technique (SEFT). Terapi SEFT ini merupakan jenis terapi yang menggabungkan mind-body dengan menekan titik-titik meridian tubuh. Diketahui pengaruh terapi Spiritual Emotional Freedom Technique (SEFT) terhadap kualitas tidur dan kecemasan pada pasien gagal ginjal kronik yang menjalani hemodialisa. Penelitian ini menggunakan metode Quasy Experiment dengan pendekatan One Group Pre-Post Test. Penelitian ini dilakukan terhadap 30 responden dengan menggunakan teknik purposive sampling. Instrumen penelitian menggunakan kuesioner kualitas tidur yaitu kuesioner Pittsburgh Sleep Quality Indeks (PSQI) dan Kuesioner kecemasan yaitu kuesioner Hamillton Anxiety Rating Scale (HARS) dan terapi penelitian menggunakan terapi Spiritual Emotional Freedom Technique (SEFT). Analisa data menggunakan analisa univariat dan bivariat dengan uji t-dependent. Hasil uji statistic nilai rerata pre-test kualitas tidur (8,60±2,027) dan post-test (4,77±1,870) sedangkan nilai rerata pre-test kecemasan (21,37±4,664) dan post-test (15,63±5,690). Diperoleh nilai p-value 0,000. Ada pengaruh yang signifikan antara terapi Spiritual Emotional Freedom Technique (SEFT) dengan kualitas tidur dan kecemasan pada pasien gagal ginjal kronik yang menjalani hemodialisa Kata Kunci: Gagal ginjal, Hemodialisa, Terapi SEFT, Kualitas Tidur, Kecemasan